An Expert System For Comprehension of Forage Crops and Utilization on Pasture System - Mongkon Ta-oun; Mohamed Daud; Mohdzohadic Mohdzohadic; Shamshudin Jusup (agriTECH, 1998)
The knowledge based of expert system for comprehension of forage crops and utilization on pasture system could be extracted from domain experts and established literatures for preparing an expert system skeleton. This system was developed by CLIPS program. The skeleton of the expert system is divided into four main parts; information, pasture management and prediction. The introduction part will help user to get general information of forage crops and the important environmental factors of many processes so that user can understand the process components in pasture establishment. The pasture management part explains the principle of managing the pasture for sustainable utility and gaining continuously and sufficiently high yield of crops and animal production. The last part is prediction part, to illustrate principle of factors and algorithms using in decision making / prediction the selection of forage crop varieties on pasture establishment; furthermore, in this part has model for predicting groundwater pollution vulnerability of the existing environment of pasture which will be established.